Studies on the genus Capparis L. (Capparaceae) in Lao PDR. IV: A new species from the Khammouan Province - Fici, Silvio; Souvannakhoummane, Keooudone; Lanorsavanh, Soulivanh; Lamxay, Vichith (Phytotaxa, 2020)
A new species of Capparis, C. florida, is described and illustrated from the Hin Nam No National Protected Area, Khammouan Province in central Lao PDR. The new species, collected in forest habitats of the Khammouan karst, belongs to sect. Monostichocalyx. It is an erect shrub characterized by the widely ovate or elliptical leaf-blade, by the flowers serial in supra-axillary rows, and by the slender ovary with evident style. Its affinities with related taxa, such as the widespread C. micracantha, are discussed and its conservation status assessed.